2020
DOI: 10.1051/e3sconf/202019708002
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption gas Heat Pump fuelled with hydrogen enriched natural gas blends: the analytical simulation model development and validation

Abstract: This study deals with the implementation of an analytical model to simulate the energy performance associated to a commercial Gas adsorption Heat Pump, when H2NG (Hydrogen Enriched Natural Gas) blends are used as fuel. In detail, a water source heat pump manufactured by Robur (GAHP-WS) has been used as a reference device for building the simulation model within the MATLAB-Simulink environment. Thereafter, the simulation results have been validated by the experimental campaign, testing on field and in actual op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Promising application of this technology is the integration in a hybrid energy system, which may combine different technologies such as RES [15] [16], heat pumps (HP) [17], CHP plants [18], Gas Absorption Heat Pumps (GAHP) fuelled with hydrogen enriched natural gas (H2NG) blends [19], boilers and BIPV (Building Integrated Photovoltaics) [20]. It has been demonstrated that this type of configuration, which couple traditional thermodynamic cycles with renewable-based devices, along with effective management and control strategy [21] [22], offers good opportunities to get higher environmental, energy and economic benefits in the short-medium term.…”
Section: Introductionmentioning
confidence: 99%
“…Promising application of this technology is the integration in a hybrid energy system, which may combine different technologies such as RES [15] [16], heat pumps (HP) [17], CHP plants [18], Gas Absorption Heat Pumps (GAHP) fuelled with hydrogen enriched natural gas (H2NG) blends [19], boilers and BIPV (Building Integrated Photovoltaics) [20]. It has been demonstrated that this type of configuration, which couple traditional thermodynamic cycles with renewable-based devices, along with effective management and control strategy [21] [22], offers good opportunities to get higher environmental, energy and economic benefits in the short-medium term.…”
Section: Introductionmentioning
confidence: 99%